3,3′-(5,5,7,12,12,14-Hexamethyl-1,4,8,11-tetraazacyclotetradecane-1,8-diyl)dipropanonitrile methanol disolvate - Cheng-Jun Hao; Yan-Hua Zhang (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, C22H42N6·2CH4O, comprises one half of a 14-membered tetraazacyclotetradecane macrocycle with cyanoethyl substituents on one of the N atoms and a methanol solvent molecule. The macrocycle lies about an inversion centre. The cyanoethyl substituents are oriented so that the cyano groups lie over opposite faces of the central cavity of the macrocycle. The methanol solvate molecules lie away from the cavity of the macrocycle and are linked to the macrocycles via O—H...N hydrogen bonds.